Método de análise térmica diferencial através da técnica de fluxo de calor conhecido - Juraitis, Klemensas Rimgaudas; Domiciano, João Baptista; Sano, Walter; Dotto, Clemêncio Teodoro (Semina: Ciências Exatas e Tecnológicas, 2004)
In this paper we presented an alternative technique for the method of Diferential Analysis. This technique used a known heat flow instead of constant heat flow. The application of this new technique simplyfies the equipment and quickens the report of data without the loss of information, but it increases difficulties for data analysis. The technique was tested in the determination of Structural Phase Transition of NiCl2.2H2O monocrystal, whose results agreed with the ones obtained from Electron Paramagnetic Resonance, Differential Thermal Expansion and Adiabatic Calorimeter Techniques.